Biotechnology of anaerobic digestion enhanced by iron-reducing bacteria - Tay, Stephen Tiong Lee. (2008)
The aim of the research project was to study and optimize anaerobic treatment of organic and sulfate-containing wastewater under different dosage of iron-containing compounds. Anaerobic sludge of municipal wastewater treatment plant can be used for enrichment culture of iron-reducing bacteria (IRB) with maximum iron reduction rate 3.5 mg/l h for ferrihydrate and 0.75 mg/l h for iron-containing clay. Iron-containing clay, iron hydroxide, and ferric pyrophosphate were studied as the sources of Fe (III) for iron-reducing bacteria. Best source for iron reduction was dissolved ferric pyrophosphate, but most reasonable source for wastewater treatment can be iron hydroxide. Iron- reducing activity of isolated pure cultures was just 60 to 70% of the activity of related enrichment cultures.